1961
DOI: 10.1080/00021369.1961.10857842
|View full text |Cite
|
Sign up to set email alerts
|

l-Homoserine Fermentation

Abstract: .In the course of studies on "negative feedback control" rnechanisnls caused by threonine and nlethionine in L-homoserine fermentation with Micrococcus glutarnicus 534:-Co147 culture, L-homoserine dehydrogenase was first found to occur in the culture, and effects of various amino acids on the formation and action of the enzyme wcre then invcstigated. The rcsult was that L-homoserine dehydrogenase of the culture was repressed by methionine on the one hand, and inhibited by threonine on the other. .a-Aspartokina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1962
1962
1990
1990

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Like aspartate fisemialdehyde dehydrogenase the homoserine dehydrogenase of Rp8. spheroides is specific for NADP+ and does not utilize NAD+; it is sinmilar in this respect to the homoserine dehydrogenase in M. glutamicus (Nara et al 1961), but different from the one in baker's yeast (Black & Wright, 1955c), which can use both nucleotides. The rate of reduction was linear for 5 min.…”
Section: Inhibition Studiesmentioning
confidence: 94%
See 2 more Smart Citations
“…Like aspartate fisemialdehyde dehydrogenase the homoserine dehydrogenase of Rp8. spheroides is specific for NADP+ and does not utilize NAD+; it is sinmilar in this respect to the homoserine dehydrogenase in M. glutamicus (Nara et al 1961), but different from the one in baker's yeast (Black & Wright, 1955c), which can use both nucleotides. The rate of reduction was linear for 5 min.…”
Section: Inhibition Studiesmentioning
confidence: 94%
“…spheroide8 the homoserine dehydrogenase can utilize only NADP, whereas the corresponding enzyme from yeast utilizes both NADP and NAD and in fact has a greater affinity for the latter. Nara et al (1961) found that the homoserine dehydrogenase from M. glutamicus also was specific for NADP. The work reported here is consistent with the postulate that threonine inhibits the production of bacteriochlorophyll in Rp8.…”
Section: Additions Nonementioning
confidence: 99%
See 1 more Smart Citation
“…(1 ) lysine-producing ability of HUT 8052, it is suggested that the mutant is a threonine plus methionine (or homoserine) auxotroph which is genetically blocked at least at 2 steps; the first step is conversion of homoserine to threonine, and the second step is homo serine dehydrogenase in the biosynthetic pathwayI6) of the amino acids of aspartic acid family (Fig, 3), Measurement of homo serine dehydrogenase activity in HUT 8052 revealed its drastic reduction in comparison with that in the wild strain (Table I) * ASA, Aspartate-/i'-semialdehyde, ** Hom" Homoserine, above, the mutant grew slightly in the absence of methionine (or homoserine) under a certain condition, Thus the block at homo serine dehydrogenase seems to be incomplete, The homoserine dehydrogenase in "glutamic acidproducing bacteria" is apt to get feedback inhibition by threonine, 15,16) Consequently, the addition of a large amount of threonine in a growth medium reduces the growth of the bacterium by inhibiting the homoserine dehydrogenase and then inhibiting the synthesis of methionine. The reduction of homoserine dehydrogenase activity would lead the strain to be more sensitive to threonine.…”
mentioning
confidence: 94%
“…154 H. KASE and K. NAKAYAMA L-Methionine has been produced by resolution of racemic DL-methionine or by hydrolysis of protein. As for microbial process, the conversion of DL-2-hydroxy-4-methylthiobutyric acid 21 or DL-5-(p-methylmercaptoethyl)-hydantoin 31 into L-methionine by various microorganisms has been reported. However, there is a dearth of report on fermentation production of L-methionine.…”
mentioning
confidence: 99%